The clinical course of symptomatic deep vein thrombosis after 3 months of anticoagulant therapy using fondaparinux/edoxaban or fondaparinux/vitamin K antagonist - Shimizu K; Iiduka T; Sato S; Kiyokawa H; Nakagami T; Mikamo H; Kawazoe M; Takahashi M; Noro M (Dove Medical Press, 2018)
Kazuhiro Shimizu, Takuo Iiduka, Shuji Sato, Hajime Kiyokawa, Takahiro Nakagami, Hiroshi Mikamo, Masayo Kawazoe, Mao Takahashi, Mahito Noro Department of Internal Medicine, Toho University Sakura Medical Center, Sakura City, Chiba, Japan Background: For the management of venous thromboembolism (VTE), providing anticoagulant therapy within the therapeutic range has been a major challenge, as conventional therapy with unfractionated heparin (UFH) and vitamin K antagonist (VKA) requires frequent laboratory monitoring and dose adjustment. Recently, fondaparinux and edoxaban are being used as beneficial alternatives to UFH and VKA.Methods: We evaluated the clinical course of symptomatic deep vein thrombosis (DVT) in patients who received the 3-month anticoagulation therapy with fondaparinux/edoxaban (Group A; n=40) in comparison with the findings from our previous experience of patients who received the fondaparinux/VKA combination (Group B; n=33).Results: In both Groups A and B, serum D-dimer was significantly improved after treatment (p<0.001). The thrombus volume assessed by quantitative ultrasound thrombosis (QUT) score was significantly reduced in both groups (p<0.001). There was no difference in the proportion of patients who were normalized (ie, disappearance of DVT) between the groups, although Group A had significantly more patients who were normalized or improved (ie, disappearance and reduction of DVT) (p<0.001). No bleeding event was observed in either group. However, in one patient in Group B, worsening of DVT and development of symptomatic PE were observed.Conclusion: Fondaparinux/edoxaban therapy is as effective as fondaparinux/VKA. This treatment has the possible advantage in thrombus regression. This would be a beneficial therapeutic option for both patients and physicians. Keywords: venous thromboembolism, deep vein thrombosis, anticoagulant therapy, quantitative ultrasound thrombosis score, FXa inhibitors